Development of a Disaster Mitigation Model Based on Local Wisdom - Ikbal, Mohammad; Syamsuddin, Adiesty Septhiany; Korompot, Ratu Ratna; Yoshida, Kunihiko (Jambe Law Journal, 2023)
In recent years, earthquake mitigation is no longer dominated by pure science, but it moves towards various approaches based on sociology and anthropology. The main question of this paper is how local wisdom affect the way the people of Palu City faced disasters before there were legal arrangements and legislation regarding disasters and how to integrate this knowledge with the legal substance formulated by the government. Despite having a disaster mitigation policy, the local community and local government showed no disaster preparedness resulting in insurmountable victims and damage, even though they already live in a disaster-prone area. Therefore, a better system based on the integration of local wisdom that is obeyed by the local community needs to be established. Local wisdom is part of the Indonesian legal system, as it can be used as a material source for legislation. Through this research, we explored the possibility of accommodating local wisdom into the government's policy in the form of legislation using a case study from Pasigala, the region that used to be most heavily impacted by the 2018 earthquake. As a result, a model of disaster mitigation based on local wisdom was created and can be implemented as a local policy